2009
DOI: 10.1007/s00125-009-1268-0
|View full text |Cite
|
Sign up to set email alerts
|

Is hyperfiltration associated with the future risk of developing diabetic nephropathy? A meta-analysis

Abstract: Aims/hypothesis Glomerular hyperfiltration is a wellestablished phenomenon occurring early in some patients with type 1 diabetes. However, there is no consistent answer regarding whether hyperfiltration predicts later development of nephropathy. We performed a systematic review and meta-analysis of observational studies that compared the risk of developing diabetic nephropathy in patients with and without glomerular hyperfiltration and also explored the impact of baseline GFR. Methods A systematic review and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
244
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 321 publications
(256 citation statements)
references
References 43 publications
7
244
2
3
Order By: Relevance
“…There are several possible explanations for the divergent results reported in the meta-analysis [7] compared with those found in the Joslin clinic study [8]. Apart from the differences in mean HbA 1c levels mentioned above, it is possible that differences in the definition of progression of albuminuria may have influenced the results ( Table 2).…”
Section: Resolution Of Hyperfiltration In Clinical Trialsmentioning
confidence: 93%
See 4 more Smart Citations
“…There are several possible explanations for the divergent results reported in the meta-analysis [7] compared with those found in the Joslin clinic study [8]. Apart from the differences in mean HbA 1c levels mentioned above, it is possible that differences in the definition of progression of albuminuria may have influenced the results ( Table 2).…”
Section: Resolution Of Hyperfiltration In Clinical Trialsmentioning
confidence: 93%
“…Three of these four studies [3,11,16] reported a significant odds ratio for the association between baseline hyperfiltration and subsequent progression to at least microalbuminuria [7]. By contrast none of the remaining six studies [2,4,9,10,15,72] in the meta-analysis that used the conventional definition of microalbuminuria demonstrated a significant odds ratio.…”
Section: Resolution Of Hyperfiltration In Clinical Trialsmentioning
confidence: 96%
See 3 more Smart Citations